Multi-objective Optimization Design of Micro-cultivator Gearbox based on NSGA-Ⅱ Algorithm - Zeng Chen; Li Bing; Wang Xiaoyong; Li Shangqing; Wu Xiankun (Jixie chuandong)
In order to improve the transmission performance and efficiency,the mathematical model is established based on the main design parameters of multi- axis micro- cultivator gearbox. Then the optimization program of the key design parameters is programmed combining the SGA,the NSGA- Ⅱ with MATLAB language. Finally,the mathematical model are optimized using this program and the optimization results are compared. The optimization results show that volume decreased respectively by 14. 13% and 15. 96% and coincidence degree are improved respectively by 4. 07% and 4. 60% by using the SGA and the NSGA- Ⅱalgorithm optimization. A good optimization effect is got and the NSGA- Ⅱ algorithm is better.